Electronically Adjustable Voltage-mode First-order Allpass Filter Using Single Commercially Available IC - Amornchai Chaichana; Surapong Siripongdee; Winai Jaikla (My University, 2019)
Abstract In this design, the use of single commercially available integrated circuit (IC), LT1228 from Linear Technology Corporation, to implement the first order allpass filter is presented. The passband voltage gain of the presented first allpass filter (APF) is unit and constant throughout the operation frequency, while the phase response is electronically tuned by changing the external DC bias current. With this property, the proposed first order filter can be used as phase shifter with microcontroller controllability. Tuning phase property is not required any matching condition. The proposed phase shifter consists of one LT1228, one capacitor and two resistors which is attractive for off the shelf implementation. Moreover, the impedance at output voltage node is exhibit low which can connect to other circuit without the requirement of external voltage buffer. The expected performances of the proposed circuit are proved by Pspice simulation using macro model parameters. Also, the quadrature sinusoidal oscillator which is designed from the connecting of the proposed filter and integrator is chosen as application example.
Keywords: All-pass filter; Analog and Mixed-Signal Circuit Design